PENODAAN AGAMA DALAM PERSPEKTIF HUKUM PIDANA DAN HAK ASASI MANUSIA DI INDONESIA - Mandala, Opan Satria; Zubaedi , Zubaedi; Suparlan , Suparlan; Munawirsajali, Munawirsajali (PRODI HUKUM TATANEGARA, 2024)
The aim of this research is to find out in detail the legal basis for religious blasphemy in Indonesian legislation in general and the Criminal Code in particular and to provide an overview of the relationship between religious blasphemy and human freedom from a human rights perspective. This type of research is normative legal research, namely examining rules or concepts related to the title of the research. The results of this research are that religion is a guide to life that comes from Almighty God to regulate human life so that human life becomes safe, peaceful and orderly. The position of religion is very sacred in society so that it cannot be disturbed or damaged by any individual or group, otherwise there will be horizontal conflict in society which can affect the unity and unity of a nation. One of the disturbances that often befalls a religion is religious desecration. This desecration can take the form of insulting religious symbols such as divinity, prophets, holy books, buildings of worship and so on. The government as the front guard in realizing security and public order regulates this in a legal regulation called the Criminal Code, in the Criminal Code there are several articles that regulate provisions related to religious blasphemy, this is very important to provide threats and deterrent effects to the public so that they do not commit crimes. actions that lead to pollution or blasphemy of religion in Indonesia.